Psychosocial Determinants of Total Knee Arthroplasty Outcomes Two Years After Surgery. Issue 10 (24th September 2020) - Lopez‐Olivo, Maria A.; Ingleshwar, Aparna; Landon, Glenn C.; Siff, Sherwin J.; Barbo, Andrea; Lin, Heather Y.; Suarez‐Almazor, Maria E.
Abstract : Objective: To evaluate the association of preoperative psychosocial and demographic factors with total knee arthroplasty (TKA) outcomes and satisfaction in patients with osteoarthritis (OA) of the knee at 24 months after surgery. Methods: A prospective cohort study of patients undergoing TKA was conducted. Outcome measures included: Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Short Form 36 (SF‐36) scores at baseline and 24 months after surgery, and patient satisfaction with TKA at 24 months. Linear regression models were performed to evaluate the association of preoperative psychosocial determinants (ie, Medical Outcome Study Social Support Scale; Depression, Anxiety, and Stress Scale; Brief COPE inventory, The Life Orientation Test‐Revised; Multidimensional Health Locus of Control; and Arthritis Self‐Efficacy Scale) on outcomes. Results: We included 178 patients. Increasing WOMAC pain scores at 24 months were associated with increasing age and body mass index (BMI); low tangible social support and low optimism were associated with higher levels of pain ( R 2 = 0.15). A decrease in WOMAC function scores was also associated with older age and higher BMI; low tangible support, increased stress, and low optimism were also associated with worse function ( R 2 = 0.22). When evaluating quality of life, lower SF‐36 physical functioning scores at 24 months were associated with age, high BMI, and comorbidity ( R 2 = 0.34). Lower SF‐36 mental functioning scores were associated with depression and low optimism ( R 2 = 0.38). Having a dysfunctional style of coping was associated with lower satisfaction with surgery after 24 months (adjusted R 2 = 0.12). Conclusion: Psychosocial factors, such as tangible support, depression, dysfunctional coping, and optimism, were associated with pain, function, and satisfaction 2 years after TKA. Perioperative programs identifying and addressing psychosocial problems may result in improvements in pain and function after TKA.